Blue collar comedy tour [videorecording (DVD)] : the movie - Harding, C. B.; Foxworthy, Jeff; Engvall, Bill; White, Ron, 1956-; Larry, the Cable Guy; Grier, David Alan, 1955 June 30-; Cagle, Chris, 1968-; Klum, Heidi (Warner Home Video, 2003)
A collection of highlights from standup comedy routines made during a tour across America during the summer of 2002. This comedy concert headlines the top names in so-called "redneck" humor: Jeff Foxworthy, Bill Engvall, Ron White, and Larry the Cable Guy. This arrives after the four performers spent two years on the road and released the best-selling comedy record.